2015
DOI: 10.1007/s11783-015-0794-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient dechlorination of 2,4-dichlorophenol in an aqueous media with a mild pH using a Pd/TiO2NTs/Ti cathode

Abstract: In this study, palladium-loaded titania nanotubes was fabricated on a titanium plate (Pd/TiO 2 NTs/Ti) for efficient electrodechlorination of 2,4-chlorophenol with a mild pH condition. The nature of Pd/TiO 2 NTs/Ti electrodes was characterized by field-emission scanning electron microscope (FESEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and cyclic voltammetry (CV) techniques. The characterization results indicated the generation of Pd 0 nanoparticles which were evenly dispersed on tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Indeed, ethanol can dissociatively chemisorb on Ag to form Ag ethoxide at room temperature [185]. Meanwhile, Du et al [24] showed that the removal rate of 2,4-DCP on Pd/TiO 2 NTs/Ti electrode decreased from 91% to 35% after 5 cycles reuse. This result was ascribed to the poisoning effect of the phenol produced and the formation of palladium oxide.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ethanol can dissociatively chemisorb on Ag to form Ag ethoxide at room temperature [185]. Meanwhile, Du et al [24] showed that the removal rate of 2,4-DCP on Pd/TiO 2 NTs/Ti electrode decreased from 91% to 35% after 5 cycles reuse. This result was ascribed to the poisoning effect of the phenol produced and the formation of palladium oxide.…”
Section: Applicationsmentioning
confidence: 99%
“…It is well-known that the presence of chlorine atoms in organic compounds is related to their toxicity [23]. Therefore, the removal of chlorine atoms from organohalogenated compounds is expected to decrease their toxicity and improve their biodegradability [24]. By selectively targeting carbon-chlorine bonds, reductive dechlorination is thus a promising approach to reduce the toxicity of chlorinated organic compounds prior to a biological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…21 Recently, novel TiO 2 nanotubes have received increasing attention owing to their large specific surface area, high chemical stability, environmentally friendly characteristics and excellent ion-exchange ability. [22][23][24] Titanium dioxide nano-electrodes have been studied as promising materials, exhibiting impressive electrochemical performance in the degradation of organic compounds in wastewater and the generation of hydrogen via water splitting. 25,26 In our previous study, we have synthesized a Ti nano electrode with a large specific surface area used for nitrate removal, which achieved a nitrate reduction efficiency around 105%-154% higher than that of the untreated electrode.…”
mentioning
confidence: 99%